2020
DOI: 10.1080/14779072.2020.1748011
|View full text |Cite
|
Sign up to set email alerts
|

PROMIS® and Neuro-QoLTM measures are valid measures of health-related quality of life among patients with familial chylomicronemia syndrome

Abstract: & David Cella (2020) PROMIS® and Neuro-QoL TM measures are valid measures of healthrelated quality of life among patients with familial chylomicronemia syndrome, Expert Review of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
0
11
2
1
Order By: Relevance
“…The following symptoms, which were mentioned by patients in the prior qualitative study, were excluded from our list of the most import symptoms: blurred vision, poor appetite, difficulty concentrating, weight loss, indigestion, muscle weakness. The 12 impacts shown in Table 1 expand upon the findings by Davidson by, for example, detailing specific impacts related to mental and emotional well-being and adding the concept of sleep disruption [ 6 ].…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The following symptoms, which were mentioned by patients in the prior qualitative study, were excluded from our list of the most import symptoms: blurred vision, poor appetite, difficulty concentrating, weight loss, indigestion, muscle weakness. The 12 impacts shown in Table 1 expand upon the findings by Davidson by, for example, detailing specific impacts related to mental and emotional well-being and adding the concept of sleep disruption [ 6 ].…”
Section: Resultsmentioning
confidence: 77%
“…Although items drawn from PROMIS have undergone cognitive debriefing to evaluate language, comprehensibility, ambiguity, and relevance [ 16 ], we conducted cognitive interviews of the draft item set with individuals with FCS to confirm item clarity, meaning, and relevance for FCS. Participants for the cognitive interviews were recruited from a sample of individuals with FCS who participated in the 2018 study, “PROMIS®-Based Survey of Health-Related Quality of Life in Familial Chylomicronemia Syndrome.”[ 6 ]. All participants reported that they had a diagnosis of FCS, were 18 years of age or older, and lived in the United States.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Impacts, too, reflect both the unpredictability and chronic course of the disease and the ways in which patients attempt to manage their FCS and its symptoms. In a recent study, patients with FCS reported both abdominal (“belly”) pain and pain interference considered clinically meaningful based on comparisons to general population norms [ 11 , 12 ]. Similar findings were also reported for cognition impacts [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, patients with FCS reported both abdominal (“belly”) pain and pain interference considered clinically meaningful based on comparisons to general population norms [ 11 , 12 ]. Similar findings were also reported for cognition impacts [ 11 ]. In the current study, worry or anxiety was a common theme when patients described ongoing impacts of FCS.…”
Section: Discussionmentioning
confidence: 99%